2020
DOI: 10.1111/tid.13364
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 in lung transplant recipients

Abstract: Solid organ transplant recipients are considered at high risk for COVID-19 infection due to chronic immune suppression; little data currently exists on the manifestations and outcomes of COVID-19 infection in lung transplant recipients. Here we report 8 cases of COVID-19 identified in patients with a history of lung transplant. We describe the clinical course of disease as well as preexisting characteristics of these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
2
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(62 citation statements)
references
References 5 publications
1
52
2
2
Order By: Relevance
“…The hospital outcomes in the largest case series from Spain were poor, with more than 80% of the patients developing respiratory failure and nearly 40% succumbing to the infection. Similarly, in New York, 34% of the LT patients with COVID-19 succumbed within 2 weeks of illness [18], while the mortality rate was 25% in a series from Philadelphia [17]. Conversely, the outcomes from the Belgian series [20] appeared to be better, although it included only 10 patients.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The hospital outcomes in the largest case series from Spain were poor, with more than 80% of the patients developing respiratory failure and nearly 40% succumbing to the infection. Similarly, in New York, 34% of the LT patients with COVID-19 succumbed within 2 weeks of illness [18], while the mortality rate was 25% in a series from Philadelphia [17]. Conversely, the outcomes from the Belgian series [20] appeared to be better, although it included only 10 patients.…”
Section: Discussionmentioning
confidence: 98%
“…The earlier series describing COVID-19 in LT patients from the United States [ 6 , 17 , 18 ] as well as from Spain [19] , Belgium [20] and France [21] reported markedly variable patient outcomes despite being from the same time period. The hospital outcomes in the largest case series from Spain were poor, with more than 80% of the patients developing respiratory failure and nearly 40% succumbing to the infection.…”
Section: Discussionmentioning
confidence: 99%
“…To be included, the study must have reported clinical data on adult (A-CA) or pediatric (P-CA) cancer patients and SOT or HCT recipients with confirmed COVID-19. Our inclusion and exclusion criteria identified 64 SOT studies, 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 11 HCT studies,…”
Section: Methodsmentioning
confidence: 99%
“…Lung Transplant Recipients (LTRs) are among the most vulnerable groups in the COVID-19 pandemic (mortality 14-39%). [1][2][3][4] An early report provided evidence of a poor antibody response after the first mRNA vaccine dose in solid organ transplant recipients. 5 However, the immunogenicity of the novel mRNA COVID-19 complete 2-dose vaccine in LTRs is unknown to date.…”
Section: Introductionmentioning
confidence: 99%